2018
DOI: 10.6090/jarq.52.255
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Effects on Supply and Demand of Rice in India

Abstract: Climate Change Effects on Supply and Demand of Rice in India production and cultivation areas are greater than those of other crops. And since 2012, India has overtaken Thailand as the world's largest rice exporter. In 2013, India's share of world rice exports was 30.1% and subject to wide fluctuations according to domestic production. The share of total exports to the total production of rice in the world was only 6.0% in 2013. Therefore, the world rice market is relatively small compared to the domestic rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The potato yield, area, imports, and demand functions were estimated based on work reported by Hung et al and Furuya et al to develop an outlook with regard to the variation in the supply and market price of potatoes as a result of climate change [30,47]. Their model's basic mathematical expressions were followed and improved for this study by adding climatic variables to generate the potato supply and demand model.…”
Section: Supply and Demand Model Of Potatomentioning
confidence: 99%
See 2 more Smart Citations
“…The potato yield, area, imports, and demand functions were estimated based on work reported by Hung et al and Furuya et al to develop an outlook with regard to the variation in the supply and market price of potatoes as a result of climate change [30,47]. Their model's basic mathematical expressions were followed and improved for this study by adding climatic variables to generate the potato supply and demand model.…”
Section: Supply and Demand Model Of Potatomentioning
confidence: 99%
“…Similarly, the yield variation was higher under Representative Concentration Pathways (RCP) 6.0 (2.0-3.7 • C) than under RCP 8.5 (3.2-5.4 • C) where each scenario is more suitable for the South Asian region, including Bangladesh [29]. Another study revealed that climate change harmed the rice yield in India; more specifically, higher temperatures lowered rice yields in most states, except for those states at high altitudes [30]. Researchers have also emphasized the supply and demand elasticities of major agricultural commodities in the U.S.A. [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effects of damage due to SBR on the supply and demand of soybeans and soybean products, we used a supply and demand model based on the models of Koizumi and Ohga [24] and Hung et al [28]. We modified the original model and used state-level data.…”
Section: Supply and Demand Model Of Soybeans And Soybean Productsmentioning
confidence: 99%
“…Johansen cointegration tests were applied in the next step if the variables had unit roots. If the variables did not have cointegrating relations, then difference functions were applied, as described in Hung et al [28].…”
Section: Supply and Demand Model Of Soybeans And Soybean Productsmentioning
confidence: 99%